Continuous Product Concept Improvement for Integrated Systems: A 3-D Printer Hardware Improvement Case. Issue 1 (August 2021) - Vashi, Yash; Wang, Chu-Yi; Karampure, Rutuja; Lu, Stephen
Abstract: The advent of globalization and technology has led to proliferation of integrated hardware and software systems such as personal computers, and smartphones while legacy systems such as automobile are increasingly incorporating software technology into their products. The demanding consumer requirements compel companies to deliver improved products on short timelines. Therefore, a partial product improvement process would assist designer in meeting this demand. This paper focuses on uncovering the drawbacks of an integrated system and suggests a methodology to improve its shortcomings. We develop a conceptual framework that highlights the key steps that a designer can consider when performing continuous product development: functional model construction, concept improvement, and improvement strategy. This paper uses a case of an FFF 3D Printer system to demonstrate the method.